2020
DOI: 10.1177/1524838020960219
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Treatment Interventions for Individuals With Intellectual Disability and Trauma Symptoms: A Review of the Recent Literature

Abstract: Individuals with intellectual disabilities (IDs) are at increased susceptibility to adverse life experiences and trauma sequelae. There is a disparate range of therapeutic interventions for post-traumatic stress disorder (PTSD) and associated symptoms. This systematic review aimed to appraise the effectiveness of both cognitive behavioral therapy (CBT) and eye movement desensitization and reprocessing (EMDR) for PTSD and associated symptoms for both adults and children with mild, moderate, or severe intellectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…In spite of the current understanding of trauma and PTSD in the intellectually disabled population, and in spite of the evidence base for the effectiveness of EMDR for the treatment of PTSD in the general population, a lack of methodologically sound research means less is known about EMDR for the treatment of people with intellectual disabilities and PTSD (Byrne, 2020), including how to adapt the standard protocol for this clinical group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of the current understanding of trauma and PTSD in the intellectually disabled population, and in spite of the evidence base for the effectiveness of EMDR for the treatment of PTSD in the general population, a lack of methodologically sound research means less is known about EMDR for the treatment of people with intellectual disabilities and PTSD (Byrne, 2020), including how to adapt the standard protocol for this clinical group.…”
Section: Discussionmentioning
confidence: 99%
“…The population of people with intellectual disabilities are known to be more likely to experience trauma (Beail et al , 2021 ; Hatton and Emerson, 2004; Mason-Roberts et al , 2018; Mevissen and de Jongh, 2010; Tsakanikos et al , 2007), and to experience environmental stressors that place them at higher risk of developing post-traumatic stress disorder (PTSD) and co-morbid mental health conditions (Wigham and Emerson, 2015). In spite of this, PTSD is not as frequently diagnosed in this population, and less is known about the application of psychological therapies for treatment of PTSD in people who have intellectual disabilities (Byrne, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence for eye movement desensitisation and reprocessing (EMDR) for people with learning disabilities and PTSD has suggested that this may be effective (Byrne, 2020). At the time of these events, this intervention was not available in the MHLDT.…”
Section: Literature: Diagnosis and Treatment Of Ptsd In People With Learning Disabilitiesmentioning
confidence: 99%
“…At the time of these events, this intervention was not available in the MHLDT. Cognitive behaviour therapy (CBT) was considered but required a level of language and abstract processing that was not possible for James and George (Byrne, 2020; Whitehouse et al., 2006).…”
Section: Literature: Diagnosis and Treatment Of Ptsd In People With Learning Disabilitiesmentioning
confidence: 99%